PERBEDAAN SELF-REGULATED LEARNING SISWA SMA BUDI AGUNG DITINJAU DARI POLA ASUH ORANGTUA - Mirawati, Mirawati; Musslifah, Anniez Rachmawati (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This study aims to see whether there are differences in high school students' self-regulated learning related to their perceptions of parenting styles. There are four types of parenting: authoritarian parenting, democratic parenting, generous parenting, and spoiled parenting. In addition, this study analyzes whether there are differences in the learning abilities of self-regulated students who tend to perceive authoritarian, democratic, indifferent, and permissive tolerance parenting styles. The research was conducted in class XI SMA Budhi Agung Madura with a total of 185 research subjects consisting of 28 students. The data collection steps were a 40-item parenting style questionnaire and a 70-item self-regulated learning questionnaire. Data analysis was performed using the one way analysis of variance (ANOVA) statistical method using the statistical program SPSS version 13 for Windows. The relevance of these two measures is based on the relevance of the content assessed by experts. The reliability of self-adjusted learning scale was 0.949, the reliability of perceptions of authoritarian parenting was 0.777, democratic: 0.730, generous did not care: 0.820, and generous was spoiled: 0.680